Choroidal Thickness Profile in Chorioretinal Diseases: Beyond the Macula - Kim, Young Ho; Oh, Jaeryung (Frontiers in Medicine, 2021)
Enhanced depth imaging optical coherence tomography (EDI-OCT) and swept-source OCT (SS-OCT) have emerged as essential diagnostic tools in the study and management of various chorioretinal diseases. Evidence from early clinical studies using EDI-OCT and SS-OCT indicates that choroidal dysfunction plays a major role in the pathogenesis of chorioretinal diseases. Measurement of choroidal thickness (CT) has already become a major research and clinical method, and CT is considered as an indicator of choroidal status in a variety of ophthalmic diseases. Recently, CT measurement has also been proposed as a non-invasive marker for the early detection and monitoring of various systemic diseases. Among the several possible CT measurement locations, subfoveal CT has rapidly become a reliable parameter for measuring CT in healthy and diseased eyes. Moreover, recent advancements in OCT technology have enabled faster and wider imaging of the posterior part of the eye, allowing the various changes in CT as measured outside the macula to be shown accordingly. In this review, we first provide an overview of the results of clinical studies that have analyzed the healthy macular choroid and that in various chorioretinal diseases, and then summarize the current understanding of the choroid outside the macula. We also examine the CT profile as an index that encompasses both within and outside of the macula. Furthermore, we describe the clinical applications of ultrawide OCT, which enables visualization of the far periphery, and discuss the prospects for the development of more reliable choroidal parameters that can better reflect the choroid’s characteristics.